Insight to the Role of Basic School Teachers in the Care of Diabetic Children, Omdurman Locality -2017 - Zakaria, Nifal Siddig Ariss; Mustafa, Wedad Alsheikh; MS, Omaima Abdelmajeed; Hassan, Mahmoud (Gezira Journal of Health Sciences; Vol 15 No 2 (2019), 2019)
Children with diabetes spend up to 8 hours a day in school, during which they require blood glucose monitoring, insulin administration and facilities to treat low blood glucose during the school day. The main objective of this study was to assess the role of basic school teachers regarding the care of diabetic children in the Omdurman locality. This is a cross-sectional school based study in the Omdurman locality, 50 schools out of 169 were selected, and 371 teachers were included in the study from total number of 1658 teachers, using a multistage sampling. A structured questionnaire was used for data collection. In this study, most of the participants were female teachers (70.4%) and aged between 30 and 60 years (77.9%); most of them were university graduates (76.5%) and they had average knowledge scores regarding DM (59.3%). The majority of the teachers knew the symptoms and signs of hypoglycemia (72.8%), but only (28%) of them had knowledge about symptoms and signs of hyperglycemia, with (54.4%) opting not to intervene and stabilize diabetic students in diabetic emergencies. Most of the schools have no qualified person(s) or clinic(s) to deal with a diabetic child (71.4%), (93%) of the teachers didn’t receive any specific training regarding the care of a diabetic child during school days, but teachers were willing to have relevant training and education (87.1%). The knowledge about diabetes among school teachers in the Omdurman area was average, despite the lack of training programs. Moreover, regarding the current situation, most schools have no health personnel to deal with a diabetic student at school, collaboration between the Ministry of Health and Education is needed to increase awareness and education levels of school teachers regarding the care of a diabetic student is a must, in addition to the establishment school health clinics.